Beyond interaction : hawker culture, food and space. - Ku, Kairong. (2010)
Beyond Interaction is a project that explores on Singapore’s hawker culture, food and space. This project accentuates Singapore’s identity and culture by recording, studying and further developing it through a mobile installation, “The Hawker Centre”. The installation aims to constitute a dialogue between the information and the audiences by using data gathered from the history, food, people and environment of hawker centres that are then mapped into infographics. Afterwards these info-graphics are translated into ideas in various forms and mediums that are reinserted into the installation. Using a mobile installation as the showcase platform, exhibit the idea of living food museum — celebrating Singapore’s dynamic and rich multi-faceted culture.